Reconnaissance attack on IPv6 to IPv4 tunneling - Bahaman, Nazrulazhar; Anton Satria, Prabuwono; Teddy , Mantoro (IGI Publishing, 2013)
Internet Protocol version 6 (IPv6) is created to occupy the insufficient current Internet addresses. Consequently this significant contribution offers huge number of Internet addresses. Besides, their security also has been improved to challenge today threats in competent on IPv6 network. As alternative, an automatic tunneling was introduced along with other transition mechanisms to ensure smooth implementation on existing network. However, it’s believed that the implementation of automatic tunneling has altered the form of the IPv4 threats. Then the gained information from this mechanism is exploited to attempt the target network. As a concern, this paper thoroughly describes on potential of reconnaissance attack reach through automatic tunneling named 6to4 Tunneling. The preference development tools and networking defense mechanism suite, is setup to conduct proposed attack method under 6to4 tunnel testbed environment. As a result, the attacking method is feasible to attempt and 6to4 tunnel showed their influence on the achievement of DoS attack in current internet.